Health mediation: an intervention mode for improving emergency department care and support for patients living in precarious conditions - Riwan Naït Salem; Michel Rotily; Themistoklis Apostolidis; Sophie Odena; Aurore Lamouroux; Célia Chischportich; Nicolas Persico; Pascal Auquier (BMC, 2023)
Abstract Background Severe overcrowding of emergency departments (EDs) impacts the quality of healthcare. One factor of this overcrowding is precariousness, but it has rarely been considered a key factor in designing interventions to improve ED care. Health mediation (HM) aims to facilitate access to rights, prevention, and care for the most vulnerable persons and to raise awareness among healthcare providers about obstacles in accessing healthcare. We here present the results of an ancillary qualitative study to explore the prospects regarding a health mediation intervention implemented in EDs for deprived persons who are frequent ED users, from professionals' and patients' perspectives. Methods Design, data collection, and data analysis were done according to a psychosocial approach, based on thematic content analysis and semi-structured interviews of 16 frequent ED users and deprived patients exposed to HM and of 14 professionals in 4 EDs of South-eastern France. Results All patients reported multifactorial distress. Most of them expressed experiencing isolation and powerlessness, and lacking personal resources to cope with healthcare. They mentioned the use of ED as a way of quickly meeting a professional to respond to their suffering, and recognized the trustworthy alliance with health mediators (HMrs) as a means to put them back in a healthcare pathway. The presence of HMrs in EDs was appreciated by ED professionals because HMrs responded to requests they were not able to access and were perceived as an efficient support for caring for deprived persons in emergency contexts. Conclusions Our results are in favour of health mediation in EDs as a promising solution, requested by patients and ED professionals, to cope with frequent ED users and deprived patients. Our results could also be used to adapt other strategies for the most vulnerable populations to reduce the frequency of ED readmissions. At the interface of the patients' health experience and the medico-social sector, HM could complete the immediate responses to medical needs given in EDs and contribute in alleviating the social inequalities of health.